Netralitas ASN dalam Perspektif Regulasi dan Etika Birokrasi di Indonesia - Fitri, Wafiq Nurul; Fania, Septa Adri; Asyifa, Siti Zikra; Parida, Parida; Hanoselina, Yulia (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
The neutrality of Civil Servants (ASN) is a fundamental principle to ensure professionalism and integrity within Indonesia’s bureaucracy. However, violations of this principle still frequently occur, especially during general elections, indicating weak law enforcement and low bureaucratic ethical awareness. This study aims to analyze the relationship between regulations and bureaucratic ethics in strengthening ASN neutrality and to evaluate the effectiveness of legal instruments in fostering the moral awareness of state officials. The research employed a qualitative approach using a literature review method. Data were collected through an examination of relevant laws and regulations, academic journals, books, and research reports sourced from academic portals such as Mendeley, Google Scholar, Garuda, and SINTA. The findings reveal that although regulations such as Law Number 5 of 2014 on ASN and the Government Regulation on the Code of Ethics provide a strong legal foundation, their implementation remains suboptimal without sufficient moral awareness among civil servants. Therefore, ASN compliance with neutrality principles must be supported not only by legal sanctions but also by continuous ethical development to foster professionalism, neutrality, and integrity in public service.